2022
DOI: 10.3390/jcm11123556
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endurance Training on Serum BDNF Levels in the Chronic Post-Stroke Phase: Current Evidence and Qualitative Systematic Review

Abstract: Research in modern neurorehabilitation focusses on cognitive and motor recovery programmes tailored to each stroke patient, with particular emphasis on physiological parameters. The objectives of this review were to determine whether a single bout of endurance activity or long-term endurance activity regulates exercise-dependent serum brain-derived neurotrophic factor (BDNF) levels and to evaluate the methodological quality of the studies. To assess the effectiveness of endurance exercise among patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
0
0
0
Order By: Relevance
“…Executive function is responsible for higher cognitive processes involved in managing other basic cognitive functions. Aerobic exercise is proposed to induce the expression of BDNF throughout the central nervous system, which in turn, can enhance synaptic plasticity (52). Research has consistently shown that aerobic exercise can elevate baseline BDNF levels in the hippocampus, striatum, and various cortical regions in laboratory animals [44].…”
Section: The Effect Of Aerobic Exercise On the Brain-derived Neurotro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Executive function is responsible for higher cognitive processes involved in managing other basic cognitive functions. Aerobic exercise is proposed to induce the expression of BDNF throughout the central nervous system, which in turn, can enhance synaptic plasticity (52). Research has consistently shown that aerobic exercise can elevate baseline BDNF levels in the hippocampus, striatum, and various cortical regions in laboratory animals [44].…”
Section: The Effect Of Aerobic Exercise On the Brain-derived Neurotro...mentioning
confidence: 99%
“…Recent research indicates that the levels of BDNF, which increase after short-term exercise, can continue to rise with long-term aerobic exercise [51]. Longterm endurance training in humans has been shown to result in an increase in resting serum BDNF levels that persist over time [52]. In contrast, some studies have reported that the duration of aerobic exercise does not have a significant influence on resting levels of serum BDNF [51,53].…”
Section: The Effect Of Aerobic Exercise On the Brain-derived Neurotro...mentioning
confidence: 99%